Kondisi Sosial Ekonomi Terhadap Kesejahteraan Keluarga Di Jawa Timur - Qatrunnada Salsabila Arum Lukluli; Hendry Cahyono Cahyono (Jurnal Ekonomika : INDEPENDEN, 2022)
This research is intended to analyze the socio-economic conditions that affect family welfare in East Java. The variables in this study consist of family welfare as the dependent variable and gender of the head of the household, level of education, and asset ownership as independent variables. This research is a quantitative study using data from the 2020 national socio-economic survey (SUSENAS). The analytical method used is binary logistic regression analysis. The results of this study are that the variables of gender and education level have a significant effect on family welfare in East Java.